1997
DOI: 10.1002/j.2164-4683.1997.tb00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Validation of the Encouragement Scale (Educator Form)

Abstract: This article describes the development and initial validation of the Encouragement Scale. Results from three studies support the internal consistency, test‐retest stability, and validity of the scores from the Encouragement Scale, and support the use of the Encouragement Scale as a research tool to measure attitudes necessary for effective personal relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…T wo psychological constructs, encouragement and ethnicity, have been the focus of numerous independent empirical investigations in the professional literature (e.g., Evans, Dedrick, & Epstein, 1997;Lingg & Wilborn, 1992;Phinney, 1988Phinney, , 1990). Reviews of the professional literature in counseling and related disciplines indicate many articles and dissertations that examine actions typically associated with encouragement and praise in relation to ethnicity (e.g., Betts, 1993;Denton, 1990;Gomez, 1994); however, none of this research examines the Adlerian construct of encouragement together with ethnicity in racially and ethnically diverse minority populations.…”
mentioning
confidence: 99%
“…T wo psychological constructs, encouragement and ethnicity, have been the focus of numerous independent empirical investigations in the professional literature (e.g., Evans, Dedrick, & Epstein, 1997;Lingg & Wilborn, 1992;Phinney, 1988Phinney, , 1990). Reviews of the professional literature in counseling and related disciplines indicate many articles and dissertations that examine actions typically associated with encouragement and praise in relation to ethnicity (e.g., Betts, 1993;Denton, 1990;Gomez, 1994); however, none of this research examines the Adlerian construct of encouragement together with ethnicity in racially and ethnically diverse minority populations.…”
mentioning
confidence: 99%
“…The ES defines encouragement as the “ability to function adequately and cope with life's challenges in a way that creates meaning and purpose in life” (Evans et al, 1997, p. 163). The scale consists of 57 items covering four subscales: View of Self, View of Others, Openness to Experience, and Sense of Belonging.…”
Section: Methodsmentioning
confidence: 99%
“…Phelps, Tranakos‐Howe, Dagley, and Lyn (2001) further described encouragement as a state of being with feelings of adequacy, competence, hope, faith, and connectedness when confronted with hardship in life. Encouraged persons have an adequate and positive view of the self and others, an openness to experience, and a sense of belonging, and “believe they are worthwhile despite how well or poorly they do and what others think of them” (Evans, Dedrick, & Epstein, 1997, p. 164). It is foreseeable that encouragement contributes to resilience.…”
mentioning
confidence: 99%
“…In the West, encouragement as a construct has been examined extensively. Dagley et al (1999), for example, proposed a three-factor structure (a positive perspective about the self, an awareness of belonging, and the courage to accept one's imperfection), whereas Evans et al (1997) suggested four factors (a positive self-view, a positive view of others, being open to experience, and a sense of belonging). In a comprehensive literature review on encouragement, Wong (2015) pointed out that "research and application on encouragement have been inconsistent over the last decades, lacking integration among various fields" (p. 179).…”
mentioning
confidence: 99%
“…Studies from both cultures, the West and South Korea, have been largely influenced by Adlerian encouragement (Adler, 1956; discussed below). For example, the Encouragement Scale (Evans et al, 1997) derives from Adler's (1956) individual psychology. Likewise, almost all empirical studies that have examined the effects of encouragement‐based counseling in South Korea have adopted the Adlerian concept of encouragement (M. Kim, 2006).…”
mentioning
confidence: 99%